Suspected Adverse Event Following Immunization with Multisystem Inflammatory Response in an Infant: A Case Report - Nivyazhini D.; Gokulakrishnan n/a; Sneha S.; Sibi Vijayakumar; Priyadarshee Pradhan (Indian Journal of Forensic Medicine and Pathology, 2026)
Vaccination is a cornerstone of preventive medicine and has significantly reduced childhood morbidity and mortality. Nevertheless, rare but serious adverse events following immunization (AEFI) may occur and require meticulous evaluation. Within hours of receiving a routine vaccination, an 11-month-old male infant experienced acute gastrointestinal distress, seizures, and cardiovascular collapse. We report a suspected serious AEFI. To determine the cause of death, a comprehensive medico-legal autopsy was performed, assisted by histopathology, cytopathology, post-mortem computed tomography (PMCT), and forensic laboratory investigations. The findings of the autopsy showed multisystem involvement, including widespread lymphocytic infiltration throughout several organs, pulmonary edema, and serous effusions. PMCT results, which showed characteristics suggestive of acute respiratory distress syndrome with pleural and pericardial effusions, supported the autopsy. The death was reported as a suspected serious AEFI requiring causality assessment by the AEFI surveillance committee in compliance with World Health Organization guidelines due to the close temporal association with vaccination, the exclusion of other causes of death, and the presence of pathological features suggestive of a multisystem inflammatory syndrome driven by immune dysregulation. The importance of forensic autopsy in determining systemic inflammatory reactions in unexplained post-vaccination deaths is highlighted by this case.